2015
DOI: 10.1016/j.livsci.2015.05.027
|View full text |Cite
|
Sign up to set email alerts
|

Close relationship between pre- and post-calving reticuloruminal pH levels in dairy cows

Abstract: a b s t r a c tThe aim of the present study was to investigate the effects of prepartum reticuloruminal pH values on postpartum pH values of lactating cows at two concentrate supplementation levels. An indwelling pH measurement system with a wireless data transmitting unit was given to 9 heifers and 11 cows orally 2 weeks before expected calving. The pH was measured from week 2 prepartum to week 6 postpartum. Prepartum, all animals were fed hay and grass silage only. After parturition the animals were assigned… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Although VFA concentrations in the rumen or blood were not measured in this study, if the rumen epithelium was improved in the dry period from the addition of molasses, it may have carried over into lactation, resulting in better rumen health. This assumption is supported by the work of Steinwidder et al (2015), who demonstrated that cows with lower mean and minimum pH values pre-calving had lower mean and minimum pH values after calving as well, suggesting that rumen health characteristics may carry over from gestation to lactation. Moreover, when standardized for DMI post-calving, cows fed the CON diet had a greater AUC at the pH threshold of 5.8, which indicates that cows fed the CON diet were experiencing a greater degree of ruminal acidosis during early lactation than cows fed the LF diet were.…”
Section: Discussionmentioning
confidence: 71%
“…Although VFA concentrations in the rumen or blood were not measured in this study, if the rumen epithelium was improved in the dry period from the addition of molasses, it may have carried over into lactation, resulting in better rumen health. This assumption is supported by the work of Steinwidder et al (2015), who demonstrated that cows with lower mean and minimum pH values pre-calving had lower mean and minimum pH values after calving as well, suggesting that rumen health characteristics may carry over from gestation to lactation. Moreover, when standardized for DMI post-calving, cows fed the CON diet had a greater AUC at the pH threshold of 5.8, which indicates that cows fed the CON diet were experiencing a greater degree of ruminal acidosis during early lactation than cows fed the LF diet were.…”
Section: Discussionmentioning
confidence: 71%